KALIGRAFI DESAKRALISASI SENIMAN MUSLIM - Anwar, Saiful (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2018)
Calligraphy is an inseparable part of Islamic civilization. In the realm of Islamic history, calligraphy occupies a special position that is very special. Therefore, calligraphy is also referred to as the ancestor of traditional Islamic visual arts. The dynamics of growth are also extraordinary. In the context of Islamic history in Indonesia, art in the form of calligraphy marks the entry of Islam in Indonesia with the discovery of archaeological data in the form of tombstones. On the one hand, calligraphy has an important role in the development of the history of civilization. But on the other hand, along with the development of calligraphy itself which then makes animals and humans as the object triggers the emergence of debate and conflict in the body of Muslims. Indeed, the issue of iconoclasm among Muslim artists is often still a wedge. Because indeed the verses in the Koran and the information from the hadith never straightforwardly explain the principles of aesthetics in artistic expression. Regardless of the debates and conflicts that occur, calligraphy is an important vehicle as a field of expression of the souls of Muslim artists as long as these artistic expressions do not deviate or contradict Islamic law which includes aspects of morality, faith, and philosophy of human life.